IoT Care: Breast Health - Payal Parshuram Patil; Snehal G. Pal (International Journal of Advanced Robotics and Automation Technology, 2024)
In today's world, taking care of your wellbeing is of most extreme significance. The multiplication of wellbeing issues could be a genuine burden on specialists around the world, making it troublesome to viably treat each persistent. To ease the burden on specialists, there have been noteworthy progressive thoughts that have changed the healthcare industry. With the movement of computer innovation, it gets to be conceivable to create comes about more precisely and quickly. This, in turn, encourages the arrangement of treatment custom-made to person patients. Identifying cancer at an early organize is still a challenge in healthcare. The World Wellbeing Organization emphasizes that the determination and disposal of cancer cells are attainable when identified in their early stages. Subsequently, the basic for early location of cancer cells emerges as a need to relieve the challenges related with cancer. Out of all the distinctive sorts of cancer, breast cancer patients are at the beat. Various ladies are helpless to breast cancer, underscoring the centrality of identifying these cancer cells to kill them from the patient's body.
Keywords: Breast cancer location; IOT; Picture handling; healthcare applications